2006
DOI: 10.1086/507842
|View full text |Cite
|
Sign up to set email alerts
|

ChandraObservations of Red Sloan Digital Sky Survey Quasars

Abstract: We present short Chandra observations of 12 bright (i < 18) z em $ 1:5 quasars from the Sloan Digital Sky Survey chosen to have significantly redder optical colors than most quasars at the same redshift. Of the five quasars with optical properties most consistent with dust reddening at the quasar redshift, four show indirect evidence of moderate X-ray absorption (inferred N H $ 10 22 cm À2 ) with a dust-to-gas ratio <1% of the SMC value. The remaining seven objects show no evidence for even moderate intrinsic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…The higher value found for dust in the lens is broadly consistent with measurements for other lens systems (Dai & Kochanek 2009), while the value for dust at the source redshift is much lower than expected from this observed correlation. However, such low dust-to-gas ratios appear to be common for intrinsic absorption features of quasars caused by quasar outflow (Hall et al 2006), which can be explained by dust evaporation due to irradiation by the central source. Thus, we cannot draw any firm conclusion about the origin of the absorption from this analysis.…”
Section: Comparison With Optical and Radio Flux Ratiosmentioning
confidence: 99%
“…The higher value found for dust in the lens is broadly consistent with measurements for other lens systems (Dai & Kochanek 2009), while the value for dust at the source redshift is much lower than expected from this observed correlation. However, such low dust-to-gas ratios appear to be common for intrinsic absorption features of quasars caused by quasar outflow (Hall et al 2006), which can be explained by dust evaporation due to irradiation by the central source. Thus, we cannot draw any firm conclusion about the origin of the absorption from this analysis.…”
Section: Comparison With Optical and Radio Flux Ratiosmentioning
confidence: 99%
“…However, it is well known observationally (yet unexplained physically) that ∼10%-30% of AGNs have (1) Xray spectra that show no absorption and (2) optical spectra that suggest obscuration (e.g., Pappa et al 2001;Panessa & Bassani 2002;Barcons et al 2003;Georgantopoulos & Zezas 2003;Caccianiga et al 2004;Corral et al 2005;Wolter et al 2005;Mateos et al 2005;Tozzi et al 2006). The opposite effect, i.e., (1) X-ray spectra that show absorption and (2) optical spectra that suggest no obscuration, has also been observed (e.g., Silverman et al 2005 found that ∼15% of X-ray hard AGNs in ChaMP are BLAGNs; other examples can be found in Comastri et al 2001;Wilkes et al 2002;Fiore et al 2003;Brusa et al 2003;Akiyama et al 2003;Silverman et al 2005;Gallagher et al 2006;Hall et al 2006;Tajer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to WLQs, there exists a population of red type 1 quasars that can be X-ray weak (e.g., Wilkes et al 2005;Hall et al 2006). Previous X-ray studies have demonstrated that quasars with the reddest optical colors at their redshifts are more likely to be X-ray absorbed than typical quasars (e.g., Wilkes et al 2005), although some of the reddest quasars may show no evidence of X-ray absorption or X-ray weakness (e.g., Hall et al 2006). These optically red quasars may be X-ray obscured by dusty gas, which also extincts the UV continuum, perhaps from a starburst disk surrounding their accreting SMBHs (e.g., Hickox & Alexander 2018).…”
Section: X-ray Weak Red Quasarsmentioning
confidence: 99%
“…The ∆(g − i) distribution for SDSS quasars is roughly Gaussian but has a distinct red tail with ∆(g − i) 0.2, which is indicative of dust reddening (Richards et al 2003). Based on the ∆(g − i) distribution, Hall et al (2006) adopted ∆(g − i) > 0.2 to select red quasars for X-ray study.…”
Section: X-ray Weak Red Quasarsmentioning
confidence: 99%